Functional plasmonic crystal nanoantennae with ultrasmall gaps and highly tunable profiles. (August 2015) - Jiang, Xiaoxiao; Gu, Qiongchan; Yang, Linjuan; Zhao, Ruoyi; Lv, Jiangtao; Ma, Zhenhe; Si, Guangyuan
Abstract: Plasmonic nanostructures with ultrasmall gaps have found extensive applications such as molecule detection, chemical/bio-sensing, and surface enhanced Raman scattering due to the considerably enhanced electric field at the plasmon resonance. Here, we demonstrate the series of geometries of plasmonic crystals with different designs and ultrasmall gaps fabricated by a single-step focused ion beam patterning process. These designs include diversiform nanoantennae and compact nanoclusters. We show smallest features down to sub-10 nm. Our approach may find special applications in plasmon-assisted sensing, imaging and waveguiding. Highlights: Fabrication of plasmonic structures with ultrasmall gaps by focused ion beam milling is shown. Nanoantennae and nanoclusters with smallest features down to sub-10 nm are achieved. Our approach may find useful applications in plasmon-assisted sensing and imaging.